Highly protective polyolefin coating modified with ceria nano particles treated with N, N, N', N'-Tetrakis(2-hydroxyethyl)ethylenediamine for corrosion protection of carbon steel. (15th April 2022) - Attaei, Mahboobeh; Taryba, Maryna G.; Shakoor, R. Abdul; Kahraman, Ramazan; Marques, Ana C.; Montemor, M. Fátima
Abstract: A polyolefin coating was modified with cerium oxide nanoparticles treated with N, N, N', N'-Tetrakis(2-hydroxyethyl)ethylenediamine (THEEDA) as corrosion inhibitor for corrosion protection of carbon steel. Electrochemical Impedance Spectroscopy tests carried out in 0.05 M NaCl revealed low-frequency impedance modulus around 10 12 Ω cm 2 for the modified coating without significant changes after three months of immersion. The self-healing ability of modified coating was studied by combining different localized electrochemical techniques, namely localized impedance spectroscopy (LEIS), the scanning vibrating electrode technique (SVET), and scanning fiber-optic dissolved oxygen microsensor. This comprehensive study confirmed the ability of ceria nanoparticles treated with THEEDA to mitigate corrosion thanks to the synergistic protective role of ceria nanoparticles and THEEDA that inhibit both cathodic and anodic activities, respectively. Graphical Abstract: ga1 Highlights: CeO2 NPs were treated with N, N, N', N'-Tetrakis(2-hydroxyethyl)ethylenediamine. Polyolefin coating was modified with the treated CeO2 NPs. Increased corrosion protection was observed for the modified coating. LEIS and SVET analysis confirmed the self-healing property of modified coatings.